Oxybelis aeneus: aggressive interactions with the clay-colored trush (Turdus grayi) - Barquero Arroyo, Marco David (2018)
In this note an aggressive encounter between a brown vine snake (Oxybelis aeneus) and a clay-colored thrush (Turdus grayi) is reported. The observations took place in the campus of the University of Costa Rica, Limón port city, Costa Rica (9° 59’4” N, 83° 3’40” W), which includes an open, grassy area, and a secondary tropical rainforest (Gutiérrez Calvo, 2012). Observations were carried out 15 m away from the interacting animals, such that individuals were not disturbed. Animals were not captured at the end of the observation period and were identified through photographs and video recorded during the interactions.